Effects of Product Prototypicality on Brand Resonance in Brand Extensions - Baird, Michael David (Curtin University, 2015)
This study investigates whether differing degrees of prototypical brands and brands that are either functional or symbolic in nature can undertake brand extensions, and if so, to what degree of congruency. The research uses a factorial design of 3 (congruency) x 2 (prototypicality) x 2 (motivation) x 2 (brand type) using four real brands. The study also creates a uni-dimensional prototypicality scale which is the first to provide a Likert type measure for prototypical brands.